2005
DOI: 10.1002/glia.20141
|View full text |Cite
|
Sign up to set email alerts
|

Failure and function of intracellular pH regulation in acute hypoxic‐ischemic injury of astrocytes

Abstract: Astrocytes can die rapidly following ischemic and traumatic injury to the CNS. Brain acid-base status has featured prominently in theories of acute astrocyte injury. Failure of astrocyte pH regulation can lead to cell loss under conditions of severe acidosis. By contrast, the function of astrocyte pH regulatory mechanisms appears to be necessary for acute cell death following the simulation of transient ischemia and reperfusion. Severe lactic acidosis, and the failure of astrocytes to regulate intracellular pH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 101 publications
(168 reference statements)
4
44
0
1
Order By: Relevance
“…While most investigators have exposed previously astrocytes to 5% O 2 , we preferred in this work to maintain astrocytes in similar conditions as neurons. Following 1% O 2 exposure, cultured astrocytes underwent rapid death, consistent with results of the other investigators, who demonstrated that astrocytes exposed to hypoxia die within 24h, hence our choice of the time profile to study astrocytes (Chesler, 2005) …”
Section: Hypoxic Exposure Of Astrocytessupporting
confidence: 86%
“…While most investigators have exposed previously astrocytes to 5% O 2 , we preferred in this work to maintain astrocytes in similar conditions as neurons. Following 1% O 2 exposure, cultured astrocytes underwent rapid death, consistent with results of the other investigators, who demonstrated that astrocytes exposed to hypoxia die within 24h, hence our choice of the time profile to study astrocytes (Chesler, 2005) …”
Section: Hypoxic Exposure Of Astrocytessupporting
confidence: 86%
“…We found that a 10-min exposure of slices to OGD had no effect on electrical coupling, suggesting a lack of significant intracellular acidification of astrocytes. This could be due to use of the stored glycogen in astrocytes to continue energy production via glycolysis (Dringen et al, 1995), maintaining the steep inwardly directed physiological Na 1 gradient for extruding H 1 via the Na 1 -H 1 exchanger and the inward Na 1 -HCO 2 3 co-transporter responsible for maintaining astrocytic intracellular pH at physiological levels (Chesler, 2005;Kimelberg, 2007;Kimelberg et al, 1990;Rose et al, 1998). The coupling was also not immediately inhibited by lowering the bath pH to 6.4, suggesting that the same pH conserving mechanisms could still function for a limited time, presumably when the energy supply is adequate (Bondarenko and Chesler, 2001;Mellergard et al, 1994).…”
Section: Gap Junction Coupling Under Ischemic Conditionsmentioning
confidence: 99%
“…Several expert reviews discuss these numerous aspects of astrocyte function and death during stroke. 4,[7][8][9][10][11][12][13][14][15] Here, we will briefly review mechanisms of astrocyte cell death during stroke, but focus most of the discussion on the adaptive and pathological roles of astrocytes during ischemia. Where applicable, we will discuss the potential for targeting astrocyte function to reduce cell death during stroke and so improve functional recovery.…”
Section: Targeting Astrocytes For Stroke Therapymentioning
confidence: 99%
“…20,21 Modeling the ion shifts that occur during stroke in combination with hypoxia and acidosis indicates that irreversible injury to astrocytes occurs in time frames as short as 15 minutes. 8 Thus, under certain conditions, astrocyte viability may be compromised very quickly in the brain, despite the relative resistance to OGD in vitro. Although in the stroke core ischemic cell death occurs very quickly, delayed increases in infarct volume are observed under some conditions.…”
Section: Mechanisms Of Astrocyte Cell Death In Strokementioning
confidence: 99%